Frauen - Liebe und Leben - Wendel-Poray, Denise; Sammlung Klöcker (Ostfildern : Hatje Cantz, 2013)
Anzinger, Siegfried; Balkenhol, Stephan; Banisadr, Ali; Böninger, Stephan; Breitling, Gisela; Brodwolf, Jürgen; Bruère, Guillaume; Cabanes, Damien; Clarke, Kevin; Cremer, Fritz; Dutoit, Isabelle; Edy, Frédérique; Einsele, Lukas; Emsbach, Bea; Fini, Leonor; Fischer, Roland; Fischl, Eric; Fräger, Markus; Freud, Lucian
Frauen - Liebe und Leben, Lehmbruck Museum, Duisberg, 21 april - 8 september 2013
boek